2014
DOI: 10.1016/j.pain.2014.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Activation of MrgC receptor inhibits N-type calcium channels in small-diameter primary sensory neurons in mice

Abstract: Mas-related G-protein-coupled receptor subtype C (mouse MrgC11 and rat rMrgC), expressed specifically in small-diameter primary sensory neurons, may constitute a novel pain inhibitory mechanism. We have shown previously that intrathecal administration of MrgC-selective agonists can strongly attenuate persistent pain in various animal models. However, the underlying mechanisms for MrgC agonist-induced analgesia remain elusive. Here, we conducted patch-clamp recordings to test the effect of MrgC agonists on high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
41
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(47 citation statements)
references
References 48 publications
6
41
0
Order By: Relevance
“…However, because these channels are broadly expressed throughout the peripheral nervous system and CNS, channel blockers pose side effects, such as nausea, anxiety, and sweating (57-59). BAM8-22 mainly inhibits N-type channels in DRG neurons from MrgprX1 mice, similar to what we found with MRGPRC activation (48). Whereas the activation of MRGPRC leads to inhibition of HVA I Ca through a phospholipase C-dependent mechanism, our findings suggest that MRGPRX1 inhibition of HVA I Ca is mainly mediated by G i/o -sensitive Gβγ binding and may also involve a Gβγ-independent pathway.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…However, because these channels are broadly expressed throughout the peripheral nervous system and CNS, channel blockers pose side effects, such as nausea, anxiety, and sweating (57-59). BAM8-22 mainly inhibits N-type channels in DRG neurons from MrgprX1 mice, similar to what we found with MRGPRC activation (48). Whereas the activation of MRGPRC leads to inhibition of HVA I Ca through a phospholipase C-dependent mechanism, our findings suggest that MRGPRX1 inhibition of HVA I Ca is mainly mediated by G i/o -sensitive Gβγ binding and may also involve a Gβγ-independent pathway.…”
Section: Discussionsupporting
confidence: 88%
“…The paired-pulse ratio (PPR) is defined as the peak amplitude of the second eEPSC (P2) divided by the first eEPSC (P1) evoked by two pulses. The reduction of first eEPSCs by BAM8-22 with ML382 was associated with an increased PPR in MrgprX1 mice, suggesting presynaptic inhibition of excitatory neurotransmitter release (48,49). This phenomenon was not observed in Mrgpr −/− mice, and ML382 alone did not affect PPR.…”
Section: Ml382 Potentiated Mrgprx1-mediated Inhibition Of Synapticmentioning
confidence: 81%
See 1 more Smart Citation
“…This feature can be of clinical interest as targeting these receptors would mainly impact nociception. It has been demonstrated that MrgC receptors are upregulated following peripheral nerve injury (He, et al, 2014a) and activation of these receptors inhibits neuropathic pain by the inhibition of synaptic neurotransmission between primary afferents and dorsal horn neurons (He, et al, 2014b;Li, et al, 2014). The present study investigated whether MrgC receptors could reverse nerve injury-induced upregulation of A C C E P T E D M A N U S C R I P T ACCEPTED MANUSCRIPT 6 pronociceptive mediators and activation of astrocytes in the spinal dorsal horn and phenotypic switching of DRG neurons.…”
mentioning
confidence: 99%
“…Intrathecal administration of agonists to MrgC (mouse MrgC11, rat homolog rMrgC) produces analgesic effects in rodent models of inflammatory and neuropathic pain(Chen et al, 2006; Guan et al, 2010a; Jiang et al, 2013; He et al, 2014b). Recent studies have begun to reveal cellular mechanisms that may underlie MrgC agonist-induced analgesia in animal models of these pain types (Jiang et al, 2013; Wang et al, 2013; Li et al, 2014). …”
Section: Introductionmentioning
confidence: 99%